Relationship Between Implant Connection and Implant Fracture: Systematic Review - Ignacio Fernández-Asián; Daniel Torres-Lagares; María-Ángeles Serrera-Figallo; José-Luis Gutiérrez-Pérez (Bioengineering)
The design of dental implants has undergone minor modifications over the years to reduce possible future complications that may arise from implant rehabilitation. One critical element from a clinical point of view is the implant connection. Given this, the team of authors of the present study decided to biomechanically analyze the effect of implant connection obtained in a possible implant fracture through a systematic review of the published literature. To this end, a search was conducted in the PubMed and Scopus databases. Only finite element studies carried out in vitro and simulation studies were included, discarding clinical studies and related reviews. A total of 19 studies were obtained for analysis and complete study. The conical type is the connection design that demonstrates the best biomechanical behavior. However, there was also significant heterogeneity in the design of the studies, which translates into a substantial source of bias, as well as different types of specific designs within the conical connection. In conclusion, it was established that the design of the connection seems to play a fundamental role in the fatigue resistance of the implant when subjected to load. However, more studies are needed to determine the most optimal specific design.